New Insights on the Use of Dietary Polyphenols or Probiotics for the Management of Arterial Hypertension - de Brito Alves, José L.; de Sousa, Vanessa P.; Cavalcanti Neto, Marinaldo P.; Magnani, Marciane; Braga, Valdir de Andrade; Costa-Silva, João H. da; Leandro, Carol G.; Vidal, Hubert; Pirola, Luciano (Frontiers in Physiology, 2016)
Arterial hypertension (AH) is one of the most prevalent risk factors for cardiovascular diseases (CD) and is the main cause of deaths worldwide. Current research establish that dietary polyphenols may help to lower blood pressure (BP), thus contributing to the reduction of cardiovascular complications. In addition, the health benefits of probiotics on BP have also attracted increased attention, as probiotics administration modulates the microbiota, which, by interacting with ingested polyphenols, controls their bioavalability. The aim of the present mini-review is to summarize and clarify the effects of dietary polyphenols and probiotics administration on BP using combined evidence from clinical and experimental studies, as well as to discuss the current debate in the literature about the usefulness of this nutritional approach to manage BP. Clinical trials and experimental studies have demonstrated that consuming dietary polyphenols or probiotics in adequate amounts may improve BP, ranging from modest to greater effects. However, the mechanisms linking probiotic intake and reduced BP levels need to be further elucidated as a definitive consensus on the link between intake of polyphenols or probiotics and improvement of AH has not been reached yet.